Fecal calprotectin in diagnosis and clinical assessment of inflammatory bowel disease. (January 2014) - Sipponen, Taina; Kolho, Kaija-Leena
Abstract The fecal neutrophil-derived biomarker calprotectin has several features of an ideal noninvasive test for detecting intestinal inflammation: it is simple, reliable, and low in cost. Its utility in differentiating inflammatory bowel diseases (IBDs) from functional conditions such as irritable bowel syndrome is well documented. Fecal calprotectin (FC) correlates closely with endoscopic activity of IBD. Emerging evidence suggest its usefulness in serial monitoring of disease activity and of therapy success in IBD. A low FC concentration predicts persistence of clinical remission especially in non-symptomatic ulcerative colitis and Crohn's colitis. Here, an overview is given to the current role of FC in diagnosis and clinical assessment of IBD.